To Identify the Hurdles and Slopes in Adoption and Implementation of Industry 4.0 Technologies in Indian Automotive Industries - Rahul Kumar Singh; Md. Nasir; Md. Imran Khan (Kurdish Studies, 2020)
Purpose: This paper focuses on jotting down all the enablers and barriers for implementation of Industry 4.0 in Production planning and control. Industry 4.0 is now growing in exponential form after the pandemic phase. All industries are willing to be connected and perform their task in much faster and efficient manner which they Industries re not doing it before. This paper will keep focus on the catalysts and impediments for implementation of Industry 4.0 for production planning and control in their organization. Design/Methodology/Approach: To find out the list of enablers and barriers with the help of fuzzy concept. Fuzzy Delphi study is done among top decision makers and by Best Worst Method it is ranked as per their importance. This study is conducted among top auto makers with qualitative approach. This paper will also emphasize on the area where others have failed and where Industries need to focus for its implementation in their industries. This paper will use statistical approach and formulations to identify the list of critical catalysts and impediments with their priority order of ranking. Findings: This paper delivers the list of barriers and enablers and their ranking among themselves based on their importance of implementation. The top raked enablers are the low hanging fruits which has to be done first in order to implement Industry 4.0 in Production planning and control and the top ranked barriers are the top hurdle which will take most of your time and energy which needs to be taken care last in order to implement Industry 4.0 in Production planning and control. Practical Implications: This study is done among top auto makers in India which made delay in the responses and this study has taken only top auto makers as its sample space. Originality/Value: The results are generated from the original work done involving the senior most members from the top auto makers of the relative field.